Frederik H. Bissinger (2021). Family Language Policies and Immigrant Language Maintenance. Lithuanian in Sweden. Stockholm Studies in Baltic Languages 13. Stockholm: Stockholm University. PhD Thesis. - Verschik, Anna (Taikomoji kalbotyra, 2023)
-